Royce and Bernstein on Evil - Viale, Claudio Marcelo (2013)
This article has a twofold purpose. On the one hand, it aims to reconstruct Josiah Royce’s views on evil. On the other hand, it intends to examine these Roycean views within the framework of Richard Bernstein’s work, particularly his books Radical Evil: a Philosophical Investigation and The Abuse of Evil. I conclude that, despite some shortcomings regarding his notion of evil, Royce’s philosophy should be recovered as a classical voice in order to fight against the abuse of evil.